Brand Awareness, Image, and Product Quality Shaping Oppo Purchase Decisions: Kesadaran Merek, Citra, dan Kualitas Produk Mempengaruhi Keputusan Pembelian Oppo - Muwafak , Muhammad Rafi; Indayani , Lilik (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rapid growth of the smartphone industry in Indonesia has created intense competition among brands to attract and retain consumers. Specific Background: Oppo has become a dominant player in the Indonesian smartphone market, supported by its strong marketing, brand image, and product innovation. However, despite its popularity, inconsistencies in previous research findings regarding the role of brand awareness, brand image, and product quality in consumer purchasing behavior reveal a Knowledge Gap. Aims: This study aims to analyze how brand awareness, brand image, and product quality contribute to purchasing decisions for Oppo smartphones in Sidoarjo. Results: Using a quantitative approach with 96 respondents and multiple linear regression, the findings show that all three variables significantly and positively influence consumer purchasing decisions. Novelty: This study integrates three core marketing constructs in one empirical model within the smartphone industry, strengthening the understanding of consumer decision-making in emerging markets. Implications: The results suggest that companies should enhance brand identity, maintain positive image perception, and improve product quality to sustain competitiveness and customer loyalty. Highlights: Brand awareness, image, and quality jointly shape consumer choices. Oppo’s marketing strength aligns with strong purchase behavior. Provides strategic insight for sustainable brand management. Keywords: Brand Awareness; Brand Image; Product Quality; Purchasing Decisions; Smartphone